Group Status Modulates the Associative Strength Between Status Quo Supporting Beliefs and Anti-Black Attitudes. Issue 7 (September 2019) - Stern, Chadly; Axt, Jordan R.
What belief systems are associated with negative attitudes toward lower status groups? Does the relationship differ across higher and lower status groups? We examined the extent to which status quo supporting beliefs (social dominance orientation and conservatism) were associated with negative attitudes toward African Americans and whether the strength of the relationship varied between members of higher and lower status racial groups. On explicit and implicit measures, status quo supporting beliefs were associated with negative attitudes toward African Americans among members of higher (White) and lower status (Black, Hispanic, and Asian) racial groups. The association was stronger among Whites than racial minorities and was stronger among Asians and Latinos than Blacks. Status quo supporting beliefs are associated with negative attitudes toward lower status groups regardless of one's group status, but the strength of the association is greatest among the societally advantaged.